RAB11FIP5 expression and altered natural killer cell function are associated with induction of HIV broadly neutralizing antibody responses - Bradley, T; Peppa, D; Pedroza-Pacheco, I; Borrow, P; al., E (Cell Press, 2018)
HIV-1 broadly neutralizing antibodies (bnAbs) are difficult to induce with vaccines but are generated in ∼50% of HIV-1-infected individuals. Understanding the molecular mechanisms of host control of bnAb induction is critical to vaccine design. Here, we performed a transcriptome analysis of blood mononuclear cells from 47 HIV-1-infected individuals who made bnAbs and 46 HIV-1-infected individuals who did not and identified in bnAb individuals upregulation of RAB11FIP5, encoding a Rab effector protein associated with recycling endosomes. Natural killer (NK) cells had the highest differential expression of RAB11FIP5, which was associated with greater dysregulation of NK cell subsets in bnAb subjects. NK cells from bnAb individuals had a more adaptive/dysfunctional phenotype and exhibited impaired degranulation and cytokine production that correlated with RAB11FIP5 transcript levels. Moreover, RAB11FIP5 overexpression modulated the function of NK cells. These data suggest that NK cells and Rab11 recycling endosomal transport are involved in regulation of HIV-1 bnAb development.